PENGUATAN KAPASITAS KLASTER USAHA KECIL DAN MENENGAH: KASUS DI SERENAN, KLATEN - D., Fereshti N.; Saputro, Edy Purwo; Purnomo, Didit (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2008)
This study aims at examining a basic and optimal strategy for strengthening an export-based UKM cluster at Serenan Klaten. This research sample is UKM bases on export in Serenan, Klaten. Reason of location choice in Serenan because Serenan has been specified to become one of UKM cluster to base on export by government. It used a qualitative approach with the identification of the export-based UKMâs characteristics. This included firm size, asset, planning, marketing, personnel, value of access to information and performance. In this research applied SWOT analysis to formulate strategy develops UKM in Serenan Klaten. There are seven strategies formulated to develop UKM in Serenan Klaten